On the best approximation of the Hölder classes by linear methods - Skorokhodov, D. S. (Reports of the National Academy of Sciences of Ukraine, 2014)
We find exact values of linear one-dimensional widths of the Hölder classes in the space C. The error of the best approximation of the Hölder classes by a wide class of linear positive methods is determined.